Medicinal plants extracts affect virulence factors expression and biofilm formation by the uropathogenic Escherichia coli - Wojnicz, Dorota (Springer-Verlag, 2012)
Medicinal plants are an important source for the therapeutic remedies of various diseases including urinary tract infections. This prompted us to perform research in this area. We decided to focus on medicinal plants species used in urinary tract infections prevention. The aim of our study was to determine the influence of Betula pendula, Equisetum arvense, Herniaria glabra, Galium odoratum, Urtica dioica, and Vaccinium vitis-idaea extracts on bacterial survival and virulence factors involved in tissue colonization and biofilm formation of the uropathogenic Escherichia coli rods. Qualitative and quantitative analysis of plant extracts were performed. Antimicrobial assay relied on the estimation of the colony forming unit number. Hydrophobicity of cells was established by salt aggregation test. Using motility agar, the ability of bacteria to move was examined. The erythrocyte hemagglutination test was used for fimbriae P screening. Curli expression was determined using YESCA agar supplemented with congo red. Quantification of biofilm formation was carried out using a microtiter plate assay and a spectrophotometric method. The results of the study indicate significant differences between investigated extracts in their antimicrobial activities. The extracts of H. glabra and V. vitis-idaea showed the highest growth-inhibitory effects (p < 0.05). Surface hydrophobicity of autoaggregating E. coli strain changed after exposure to all plant extracts, except V. vitis-idaea (p > 0.05). The B. pendula and U. dioica extracts significantly reduced the motility of the E. coli rods (p < 0.05). All the extracts exhibited the anti-biofilm activity.